1993
DOI: 10.1038/ki.1993.227
|View full text |Cite
|
Sign up to set email alerts
|

Role of the renin-angiotensin system on the renal functional reserve in renal transplant recipients

Abstract: To determine the renal functional reserve in renal transplant recipients, we measured the glomerular filtration rate by inulin clearance and the renal plasma flow by PAH clearance before and during an amino acid infusion (Totamine, 6 to 8 mg/kg/min for 90 to 120 min) in 18 transplanted patients with stable renal function. To test the role of the renin-angiotensin system on the renal functional reserve, we performed a crossover placebo-controlled randomized trial of acute blockade of the renin-angiotensin syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…Shokier et al [12] studied RFR Renal length (cm) in relation to the stimulated GFR (ml/min) in children following renal Tx after infusion of dopamine and amino acids and found lower baseline values and a somewhat lower RFR than we did. Our findings are in agreement with studies in adult renal Tx recipients investigated after an infusion of amino acids [21,22]. Rondeau, et al [21], however, showed a less pronounced increase in cyclosporine-treated patients than in azathioprine-treated patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Shokier et al [12] studied RFR Renal length (cm) in relation to the stimulated GFR (ml/min) in children following renal Tx after infusion of dopamine and amino acids and found lower baseline values and a somewhat lower RFR than we did. Our findings are in agreement with studies in adult renal Tx recipients investigated after an infusion of amino acids [21,22]. Rondeau, et al [21], however, showed a less pronounced increase in cyclosporine-treated patients than in azathioprine-treated patients.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in agreement with studies in adult renal Tx recipients investigated after an infusion of amino acids [21,22]. Rondeau, et al [21], however, showed a less pronounced increase in cyclosporine-treated patients than in azathioprine-treated patients. Other studies report no RFR in cyclosporine-treated patients [9 -11, 23].…”
Section: Discussionsupporting
confidence: 94%
“…Mogensen and Christensen (12) reported that in type 1 diabetes, global hyperfiltration is predictive of clinical proteinuria, and Sackmann et al (13) reported a reduced functional reserve both in normotensive, normoalbuminuric subjects with recent type 1 diabetes (those prone to nephropathy displayed global hyperfiltration), and in proteinuric subjects with long-lasting type 1 diabetes (those with an already reduced GFR). The participants with microalbuminuria studied by these authors were on ACE inhibitors, making data interpretation difficult, since ACE inhibitors can alter kidney function of such patients (16), and since renal functional reserve can be altered by these drugs (17). Studies conducted in animals (18,19) support the view that the glomeruli of subjects such as those with reduced functional reserve undergo individual hyperfiltration, a hemodynamic condition that favors glomerulosclerosis, hypertension, and high renovascular risk (1,11).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that grafts were able to conserve a functional reserve, but no one seems to have made such measurements in very long‐term transplant recipients. RFR was 11.6 mL/min/1.73 m 2 at 5 yr for ter Wee et al [17] and 9.7 mL/min/1.73 m 2 at 5 yr for Rondeau et al [18]. The mean RFR value found for our patients, i.e., +6.7 mL/min/1.73 m 2 (range: 0.6–19.1) is coherent with those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%